EXPRESSIVE ILLOCUTIONARY ACT IN THE MOVIE ENTITLED MALEFICENT - Utami, Ni Wayan Dina Sari; Winaya, I Made; Udayana, I Nyoman (Udayana Journal of Social Sciences and Humanities, 2024)
The title of this study is “ Expressive Illocutionary Act in the Movie Entitled Maleficent” . Based on the problems formulated, this study is aimed at identifying the types of expressive illocutionary acts found in Maleficent movie, and to analyze the context of situation in Maleficent movie. The data was taken from the utterances in the movie entitled Maleficent and explained in descriptive qualitative method. There were two major theories used in conducting  this study. The fisrt theory was propsed by Searle (1976) about the types of expressive illocutionary acts. The other theory from Holmes (2013)  was applied to explain the context of situation of the utterances. The results of the analysis showed that based on the movie Maleficent, all types of expressive illocutionary act are used by the characters to show certain expression. All data in this study consist of all components of context of situation proposed by Holmes such as the participants, the settings, the topic and the function.   Keywords: Speech act, illocutionary acts, types of expressive, context of situation